Acute effects of different stretching and warm up protocols on some anaerobic motoric tests, flexibility and balance in junior male judokas - Özgür Eken; Mehmet Z. Özkol; Saadet R. Varol (IP Iermakov S.S., 2020)
Background and Study Aim: The aim of this study is to investigate acute effects of different warm-up and stretching protocols, on 30 m. sprint, flexibility, vertical jump, strength, balance and anaerobic power performances in junior male judokas. Material and Methods: Twenty sub-elite 11-14 year old judokas who volunteered to participate in the study (age: 12,25±0,96 years; height: 1,52±0,11cm; body mass: 48,06±14,22 kg). This study consist of four different stretching and warm up protocols; without stretching (WS); static stretching (SS); dynamic warm up (DW); dynamic+static warm up (DSW). Results: The effect of the four stretching and warm up protocols were analysed by an ANOVA for repeated measures (WS x SS x DW x DSW). After stretching and warm up protocols, 30 m. sprint values are statistically significance (p<0.05). There was find statistically significant between WS and DSW, SS and DW, DW and DSW (p<0.05). There were no significant difference is found on flexibility values between four stretching and warm up protocols (p>0.05). There was only significant difference is found between WS and SS (p<0.05). Altough leg strength performance wasn't statistically significant (p>0.05), there was found significant differences between WS and DSW, SS and DSW in favour of DSW (p<0.05). Other parameters like vertical jump, balance and back strength performance weren't statistically significant after four stretching and warm up protocols. Conclusions: Consequently it is suggested for coaches and judokas that SS are required for developing flexibility performance and DSW can suggest for leg strength improvement.